Morphological and physiological traits as indicators of drought tolerance in tallgrass prairie plants - Tucker, Sally Sue (Kansas State University, 2010)
The Konza Prairie in northern Kansas, USA contains over 550 vascular plant species; of which, few have been closely studied. These species are adapted to environmental stress as imposed by variable temperature, precipitation, fire, and grazing. Understanding which plant traits relate to drought responses will allow us to both predict drought tolerance and potential future shifts in plant community composition from changes in local climate. Morphological and physiological measurements were taken on 121 species of herbaceous tallgrass prairie plants grown from seed in a growth chamber. Gas exchange measurements including maximum photosynthetic rate, stomatal conductance to water vapor, and intercellular CO[subscript]2 concentration were measured. All plants were exposed to a drought treatment and were monitored daily until stomatal conductance was zero. At this point, critical leaf water potential (Ψ[subscript]crit), an indicator of physiological drought tolerance was assessed. Other measurements include root length, diameter, volume, and mass, leaf area, leaf tissue density, root tissue density, and root to shoot ratio. Traits were compared using pair-wise bivariate analysis and principal component analysis (PCA). A dichotomy was found between dry-adapted plants with thin, dense leaves and roots, high leaf angle, and highly negative Ψ[subscript]crit and hydrophiles which have the opposite profile. A second axis offers more separation based on high photosynthetic rate, high conductance rate, and leaf angle, but fails to provide a distinction between C[subscript]3 and C[subscript]4 species. When tested independently, grasses and forbs both showed drought tolerance strategies similar to the primary analysis. Matching up these axes with long term abundance data suggests that species with drought tolerance traits have increased abundance on Konza, especially in upland habitats. However, traits that relate to drought tolerance mirror relationships with nutrient stress, confounding separation of low water versus low nutrient strategies. My results not only illustrate the utility of morphological and physiological plant traits in classifying drought responses across a range of species, but as functional traits in predicting both drought tolerance in individual species and relative abundance across environmental gradients of water availability.
Keywords: Tallgrass prairie; Drought tolerance; Plant traits; Abundance; Konza; Biology, Ecology (0329); Biology, Plant Physiology (0817)